Patients' Satisfaction of Smile Line Beauty after Maxillofacial and Oral Surgery - Reza Tabrizi; Masih Lazar; Navid Ahmadi (Mashhad University of Medical Sciences, 2021)
Introduction: The aim of this study was to assess various smile line problems and treatments and to assess the patients' satisfaction after treatment. Methods: This cross-sectional study assessed patients who had smile line problems. Various smile line problems included vertical maxillary excess (VME), muscle hyperactivity, gingival hyperplasia, short lip, bimaxillary protrusion, asymmetric muscle hyperactivity, maxillary canting, and tooth deformity. All patients filled out a questionnaire one year after the procedures for 23 assessments of satisfaction. The level of satisfaction was evaluated using a visual analog scale (VAS): 0-3 dissatisfaction, 4-7 acceptable, and 7-10 desirable.  Results: One-hundred thirty-seven patients were included in this study. The highest level of satisfaction was noted in patients who had tooth deformity, VME with passive eruption, and gingival hyperplasia or passive supra-eruption (7.75±0.46, 7.66±0.72, and 7.50±0.55, respectively). The lowest level of satisfaction was noted in patients who had asymmetric muscle activity, muscle hyperactivity, and VME+ muscle hyperactivity (4.25±0.96, 4.33±0.78 and5.00±1.09, respectively). Conclusion: Patients with soft tissue problems of the smile line may have low 41satisfaction especially when temporary treatments such as botulinum toxin are used for treatment. Surgery of the hard tissues may result in moderate to high satisfaction in patients with smile line problems.